Enhancing learners’ emotions in an L2 context through emotionalized dynamic assessment - Abdolrezapour, Parisa; Tavakoli, Mansoor; Ketabi, Saeed (Studies in Second Language Learning and Teaching, 2013)
The aim of this study was to gain more in-depth understanding of students’ emotions in an EFL context by applying dynamic assessment (DA) procedures to the development of learners’ emotional intelligence. The study with 50 intermediate learners aged 12-15 used three modalities: a control group, which was taught under institute’s normal procedures; a comparison group, which received DA; and an experimental group, which received emotionalized dynamic assessment (EDA) procedures, in the form of an intervention focusing on emotional characteristics of Goleman's emotional intelligence framework with the express purpose of inducing them to work with their emotions. The study shows the potential of EDA for increasing one’s emotional intelligence and affords practical guidelines to language teachers as to how to incorporate behaviors relating to emotional intelligence into assessment procedures